IMPROVEMENT OF PHYSICS ACTIVITIES AND LEARNING OUTCOMES THROUGH NUMBERED HEADS TOGETHER COOPERATIVE LEARNING IN CLASS XI MIPA3 SMA 2 TEMBILAHAN - Yasni, Yasni (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2020)
Â The quality of learning in the classroom is stated to be good if the learning objectives are achieved which is marked by increased student activity and learning outcomes. For that, we need alternative learning strategies that are more effective and efficient, one of which is to use the cooperative learning model type Numbered Heads Together (NHT). This study aims to improve the activity and learning outcomes of physics on wave material through the application of the NHT learning model. The research subjects were students of class XI MIPA3 of SMA Negeri 2 Tembilahan. This research is a classroom action research conducted in 2 cycles. Data collection instruments used were activity observation sheets and written tests of learning outcomes in the form of daily tests with data collection techniques in the form of observations and giving the test. The data analysis technique used is descriptive analysis to determine the extent of increased student activity and learning outcomes by applying the NHT learning model. The results of data analysis obtained an increase in student learning activities in the first cycle from 29.60% increased to 66.40% in the second cycle with a very good category. Improved learning outcomes from 12 students completed with a percentage of 48.00% in the first cycle, to 19 students who completed the second cycle with a percentage of 76.00%. Thus it can be concluded that the use of the NHT learning model can improve the activities and physics learning outcomes of students of class XI MIPA3 in SMA Negeri 2 Tembilahan on wave material.